2008
DOI: 10.1111/j.1600-0609.2008.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of DKK‐1 correlate with the extent of bone disease in patients with multiple myeloma

Abstract: Using a large series of myeloma patients, we could show for the first time a correlation between DKK-1 serum concentration and the amount of lytic bone disease, indicating that DKK-1 is an important factor for the extent of bone disease and supporting the hypothesis of DKK-1 as a therapeutic target in myeloma bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 25 publications
(40 reference statements)
3
96
0
2
Order By: Relevance
“…It is reported that alterations of circulating DKK-1 protein levels have been shown to be associated with various diseases such as multiple myeloma, rheumatoid arthritis, breast cancer, lung cancer, and esophageal cancer patients. [12][13][14][15][16] However, there is no documented study to associate circulating DKK-1 levels with DR. There is also no information available concerning the DKK-1 level in the vitreous fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that alterations of circulating DKK-1 protein levels have been shown to be associated with various diseases such as multiple myeloma, rheumatoid arthritis, breast cancer, lung cancer, and esophageal cancer patients. [12][13][14][15][16] However, there is no documented study to associate circulating DKK-1 levels with DR. There is also no information available concerning the DKK-1 level in the vitreous fluid.…”
Section: Discussionmentioning
confidence: 99%
“…11 DKK-1 is a secreted protein and readily detectable in the circulation. [12][13][14][15][16] Therefore, it is hypothesized that DKK-1 levels in circulation or ocular fluid could be associated with the development and progression of DR.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high levels of DKK1 in patients' serum are associated with poor prognosis in various cancers including oesophageal squamous cell carcinoma [136] , lung cancer [137] , breast cancer [138] and cervical cancer [138] , suggesting that the serum level of DKK1 may also reflect the prognosis of HCC patients. In multiple myeloma, high DKK1 serum levels are associated with osteolytic bone lesions [139] and patients responding to anti-myeloma treatment show a decrease in DKK1 serum levels [140] , suggesting the involvement of DKK1 in this aspect. Recently, Fulciniti et al [141] evaluated the effect of anti-DKK1 monoclonal antibody (BHQ880) in a multiple myeloma mouse model and found that it induced bone formation and inhibited tumour-induced osteolytic bone lesions.…”
Section: Dkk1mentioning
confidence: 99%
“…85 Bone marrow plasma Dkk-1 levels were increased in MM patients, and associated with Dkk-1 concentrations in peripheral blood, levels of Dkk-1 transcripts in myeloma cells and the presence of osteolytic lesions. [86][87][88] Gene expression studies in 171 newly diagnosed MM patients showed that overexpression of Dkk-1 correlated with the degree of osteolytic bone disease. 89 Similarly, serum Dkk-1 levels were elevated in myeloma patients with lytic bone disease compared with those without lytic lesions by conventional radiography, and also correlated with the number of bone lesions.…”
Section: Correlations Of Bone Turnover Markers With Myeloma Activity mentioning
confidence: 99%